(х+67-36)-88=12
х+67-36=12+88
х+67-36=100
х=100+36-67
х=136-67
х=69
Это число он и загадал
2) 12+14*2-22=128
х=128-12-28+22
х=110
3) <span>х+56:х=14+64:х:х</span>
<span> 1+56:1=14+64:1:1</span>
<span> 57=78</span>
<span>1 не явл. корнем уравнения</span>
<span> 2+56:2=14+64:2:2</span>
<span> 30=30</span>
<span>2 явл. корнем уравнения</span>
<span>4+56:4=14+64:4:4</span>
<span>18=18</span>
<span>4 явл. корнем уравнения</span>
<span>8+56:8=14+64:8:8</span>
<span>15=15</span>
<span>8 явл. корнем уравнения</span>
5х-3=37
5х=37+3
5х=40
х=40:5
х=8
5х-3=52
5х=52+3
5х=55
х=55:5
х=11
5х-3=187
5х=187+3
5х=190
х=190:5
х=38
5х-3=22
5х=22+3
5х=25
х=25:5
х=5
10,2; 0,154; 6,03; 6,201; 0,012; 10,709.
8-4целых т3/11=7целых 11/11-4целых 3/11=3целых 8/11